ANALISIS PENGARUH LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASIONAL DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Pada Karyawan Bagian Produksi PT. Apac Inti Corpora, Bawen) - Alvina, Tita Isni; Djastuti, Indi (Diponegoro Journal of Management, 2018)
This research is based on the phenomenon in the company by the high number of employee turnover and absenteeism. It indicates that there is a decline in the organizational commitment. Work environment and organizational culture are several factors that can enhance organizational commitment. This study aims to analyze the relationship between work environment and organizational culture to organizational commitment, with job satisfaction as intervening variable. This research was conducted using survey method which the data was collected through the distribution of questionnaires to 98 employees in spinning B division, part of production division PT. Apac Inti Corpora with the characteristics of permanent employees who have worked more than 1 year. Technique of sampling using non probability sampling that is purposive sampling. The method of data analysis that used is multiple regression, path analysis, and sobel test for the mediation effect.The result showed that, work environment has positive and significant effect on the job satisfaction and organizational commitment. Organizational culture has positive and significant effect on job satisfaction and organizational commitment. Job satisfaction has positive and significant effect on organizational commitment. And, job satisfaction is proven as mediator relationship between work environment and organizational culture to organizational commitment.